Abundance of native fishes, wild introduced salmonids, and escaped farmed rainbow trout in a Patagonian reservoir - Cussac, Victor Enrique (2014)
Salmonid introduction in Patagonia has caused a notorious impact on lakes and a major impact on streams, where native fishes seem to have been displaced almost completely by rainbow trout Oncorhynchus mykiss. From another perspective, the introduced salmonid species have originated wild populations that sustain an economically important sport fishery. The wide distribution of escaped farmed rainbow trout, its high abundance, and a clear decrease in the abundance of native and successfully introduced salmonid species in the Alicura Reservoir were all observed comparing recent with 1993-1995 data corresponding to littoral gillnet captures. Therefore both, native fish and introduced salmonids seem to have been drastically reduced in the presence of farmed escapees. Present results regarding fish escapes deserve to be considered when the time comes to make decisions about cage culture in other Patagonian reservoirs.